Is There a Relevant Clinical Impact in Differentiating Idiopathic versus Unexplained Male Infertility? - Christian Corsini; Luca Boeri; Luigi Candela; Edoardo Pozzi; Federico Belladelli; Paolo Capogrosso; Giuseppe Fallara; Nicolò Schifano; Daniele Cignoli; Eugenio Ventimiglia; Alessia D’Arma; Massimo Alfano; et al. (The World Journal of Men's Health, 2023)
Purpose: Overall, male factor infertility (MFI) accounts for up to 50% of etiologies of couple’s infertility, with almost 30% of MFI cases being idiopathic in nature. Idiopathic MFI does not support a tailored treatment work-up in clinical practice. To investigate rates of and characteristics of men presenting for idiopathic versus unexplained primary infertility as compared with same-ethnicity, age-comparable fertile men. Materials and Methods: Demographic, clinical and laboratory data from 3,098 primary infertile men consecutively evaluated were analyzed and compared with those of 103 fertile controls. Idiopathic male infertility (IMI) was defined for abnormality at semen analysis with no previous history of diseases affecting fertility and normal findings on physical examination and genetic and laboratory testing. Unexplained male infertility (UMI) was defined as infertility of unknown origin with completely normal findings at semen analysis. Descriptive statistics and logistic regression models tested the association between clinical variables and idiopathic infertility status. Results: Overall, 570 (18.5%) and 154 (5.0%) patients depicted criteria suggestive for either IMI or UMI, respectively. Groups were similar in terms of age, BMI, CCI, recreational habits, hormonal milieu, and sperm DNA fragmentation indexes. Conversely, testicular volume was lower in IMI (p<0.001). Vitamin D3 levels were lower in IMI vs. UMI vs. fertile controls (p=0.01). At multivariable logistic regression analysis only vitamin D3 deficiency (OR, 9.67; p=0.03) was associated with IMI. Characteristics suggestive for IMI versus UMI were observed in almost 20% and 5% of men, respectively. Overall, clinical differences between groups were slightly significant and certainly not supportive of a tailored management work-up. Conclusions: Current findings further support the urgent need of a more detailed and comprehensive assessment of infertile men to better tailoring their management work-up in the everyday clinical setting.